DESKRIPSI PROSES MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN PEMAHAMAN FAKTUAL DITINJAU DARI TINGKAT EFIKASI DIRI PADA SISWA KELAS VII SMP NEGERI 1 KOTABARU (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
ABSTRAKOne factor that determines the success of the students in learning is self-confidence(self-efficacy). Self-efficacy may affect the form of the activities, objectives and efforts ofstudents in solving problems, especially in terms of thinking. Different confidence will leadto a tendency to think different between the students and other students. The purpose ofthis study was to determine the process of solving problems of Mathematics Based onfactual understanding of students.This research is a descriptive qualitative approach. Researchers act as the maininstrument guided by test superitem, self-efficacy scale and interview guides valid. Datacollected through the provision of testing and verified by interview. Subjects were studentsof class VII SMP Negeri 1 Kotabaru consisting of four people (two subjects with highefficacy and two subjects with low efficacy). The research process followed the steps of: (a)formulate indicators Understanding of factual (b) to formulate supporting instruments(tests superitem, the scale of self-efficacy, and interview guides) are valid and reliable, (c)making the subject of research by the state of self-efficacy , (d) data collection to reveal thelevels of thinking student with test superitem, (e) perform triangulation method to obtainvalid data, (f) perform data analysis (g) discussing the results of data analysis, (h)withdrawing the conclusion of research.The results showed: (a) subject to the efficacy of high showed a tendency to thinkat an abstract level expanded, (b) subject to the low efficacy showed a tendency to thinkthe relational level, (c) subject to the efficacy of high and low show berpikiryang sameinclination relative to the tingkatunistruktural, multistruktural, and relational andpropensity to think differently on abstract levels expanded